The impact of the resource and environmental factors on the economic development of Russian regions. (November 2021) - Komarova, A.V.; Filimonova, I.V.; Novikov, A.Y.
Abstract: Ecological regulation and environmental protection are essential elements of the directions of energy and economic policy at the present stage. In some cases, the increasing environmental regulation can negatively affect economic growth, however a number of modern studies proves the opposite. Moderate environmental standards lead to the effect of innovation compensation, which has a positive effect on the micro and macro level. In this paper the influence of resource, ecological and other factors on the economic development of Russian regions is studied using panel data models with fixed and random effects. The influence of the ecological factor is revealed by including various indicators of the concern for the quality of the environment, after which the results are compared. In three of the four types of constructed models, the influence of the environmental factor, expressed by different indicators, is positive. The positive result can be explained by the fact that regulation in Russia remains quite liberal to the companies, and the threshold at which strict standards begin to slow down economic growth has not yet been passed. Other significant factors for the growth of regional economies are the availability of fixed assets, the number of employees, and the share of resource industries in gross added value.